Developmental Ethanol Exposure Causes Reduced Feeding and Reveals a Critical Role for Neuropeptide F in Survival - Guevara, Amanda; Gates, Hillary; Urbina, Brianna; French, Rachael (Frontiers in Physiology, 2018)
Food intake is necessary for survival, and natural reward circuitry has evolved to help ensure that animals ingest sufficient food to maintain development, growth, and survival. Drugs of abuse, including alcohol, co-opt the natural reward circuitry in the brain, and this is a major factor in the reinforcement of drug behaviors leading to addiction. At the junction of these two aspects of reward are alterations in feeding behavior due to alcohol consumption. In particular, developmental alcohol exposure results in a collection of physical and neurobehavioral disorders collectively referred to as Fetal Alcohol Spectrum Disorder. The deleterious effects of developmental alcohol exposure include intellectual disabilities and other neurobehavioral changes, including altered feeding behaviors. Here we use Drosophila melanogaster as a genetic model organism to study the effects of developmental alcohol exposure on feeding behavior and the expression and function of Neuropeptide F. We show that addition of a defined concentration of ethanol to food leads to reduced feeding at all stages of development. Further, genetic conditions that reduce or eliminate NPF signaling combine with ethanol exposure to further reduce feeding, and the distribution of NPF is altered in the brains of ethanol-supplemented larvae. Most strikingly, we find that the vast majority of flies with a null mutation in the NPF receptor die early in larval development when reared in ethanol, and provide evidence that this lethality is due to voluntary starvation. Collectively, we find a critical role for NPF signaling in protecting against altered feeding behavior induced by developmental ethanol exposure.